The Effects of Recruitment, Selection, and Training Practices on Employee Performance in the Construction and Related Industries - Rashed Aldhuhoori; Khalfan Almazrouei; Ahmad Sakhrieh; Muataz Al Hazza; Mohammed Alnahhal (Civil Engineering Journal, 2022)
The human resource management of a company is important in today's competitive business environment because employees are the support of the company. The performance of employees is crucial to the success of any corporation. Therefore, this study aims to identify the factors that contribute to better employee performance (EP). In this study, recruitment, selection, and training strategies are examined for their influence on EP in the UAE public sector, including the construction and related industries. Researchers used a structured questionnaire, a deductive approach, and a survey strategy to conduct the research. In this quantitative study, cross-sectional data was collected using the mono method. A sample size of 151 employees from the UAE public sector was used for this study. SPSS (statistical software) has been used to analyze the collected data. The analysis of the study confirmed a direct positive link between recruitment procedure (RP), effective selection (ES), training, and EP. The outcomes also showed a robust effect of ES on EP. In UAE public-sector corporations, training appears to be the least significant factor influencing EP. Public sector employers, such as construction and related industries in the UAE, should consider the significance and selection of enhanced EP. Doi: 10.28991/CEJ-2022-08-12-012 Full Text: PDF